Effects of carotenes and alpha-tocopherol in crude palm oil on layer and broiler chicken performance - Akter, Yeasmin (2015)
Commercial poultry producers use vegetable oils in poultry diets to supply a higher amount of dietary energy at an economically justifiable cost. Vegetable oils such as corn oil, canola oil and soybean oil are rich in unsaturated fatty acids (UFAs) which are more prone to lipid peroxidation. Oxidation of lipid causes serious damage to the poultry and its products. For this reason, poultry diets with an increased amount of vegetable oils should be supplemented with antioxidants, so that they may provide protection to the poultry and its products from oxidative damage. Crude palm oil (CPO) contains a vast amount of natural antioxidants such as carotenoids and vitamin E. The combination of high antioxidants and saturated fatty acids gives palm oil a higher oxidative stability than other vegetable oils. In this context, the objectives of this study were to investigate the antioxidant potency of CPO when fed to chicken and its effects on laying performance, egg quality, hatchability, and meat quality. To achieve the objectives, five experiments were conducted at the Poultry Unit, Department of Animal Science, Universiti Putra Malaysia. In the first experiment, CPO was supplemented in layer diets at 0, 1.5, 3 and 5% levels, and the diet with 3% CPO significantly increased (P<0.05) egg production (88.89%) and improved feed conversion ratio (1.92). Yolk color score and carotene concentrations were significantly increased (P<0.05) with increasing levels of CPO in the diet, whereas lipid peroxidation (TBARS) values in yolk followed the opposite (P<0.05) trend. Diet containing 3% CPO showed maximum deposition of α- tocopherol (96.99 μg/g) in the yolk, while yolk cholesterol and serum lipid profiles were not significantly influenced (P>0.05) by dietary CPO. In the second experiment, experimental birds were assigned to three dietary treatments namely, control, 3 and 5% CPO. The inclusion of 3% CPO in the maternal diet significantly increased (P<0.05) fertility (87.22%) and hatchability (77.31%). Liver and muscle carotene concentrations (5.29 and 3.12 μg/g ) of day old chicks from the 5% CPO fed hens were highest (P<0.05), while the maximum (P<0.05) deposition of α- tocopherol (25.41 μg/g) was found in the muscle of day old chicks obtained from the 3% CPO fed group. The lipid peroxidation (TBARS) values in the liver of day old chicks were significantly decreased (P<0.05) by the CPO supplemented maternal diets. In the third experiment, the hatching eggs produced during the second experiment were stored at 18°C for 7, 10 and 14 days to observe the effect of storage duration and carotenes and α-tocopherol in CPO on egg quality, hatchability and chick quality. The concentration of TBARS in stored eggs was significantly higher (P<0.05) in the control group compared to the CPO treated groups. Hatchability rate decreased with increased storage time, while the highest (P<0.05) hatchability rate was noticed in the 3% CPO followed by the 5% CPO and control groups. The fourth and fifth experiments were conducted to evaluate the influence of carotenes and α- tocopherol in CPO on carcass characteristics and meat quality of slow and fast growing broiler chicken. The oxidative stability, water holding capacity and tenderness value of meat from both slow and fast growing chickens were improved (P<0.05) by the dietary CPO. In slow growing chicken, meat produced in the 5% CPO fed group deposited maximum (P<0.05) amount of carotene (1.48 and 1.41 μg/g), whereas α-tocopherol content (15.34 and 23.93 μg/g) was highest in the meat of chicken fed 3% dietary CPO compared to other diets. In contrast, feeding fast growing broiler chicken with 4% CPO showed highest carotene (1.67 and 1.75 μg/g) and α-tocopherol concentrations (10.05 and 11.20 μg/g) in the meat than those fed other diets. However, the cholesterol and saturated fatty acids (SFAs) contents in meat from both slow and fast growing chickens did not show any remarkable alteration (P>0.05) due to CPO in chicken diets. The results of this study indicate that supplementation of 3-4% CPO in the chicken diets could be effective for increasing egg production, feed efficiency and for improving fresh and stored egg quality, hatchability and meat quality of chicken. Therefore, dietary CPO could be an alternative, effective and natural way in reducing the chance of lipid peroxidation of poultry and its products.